Different hormonal response to continuous and intermittent exercise in middle-distance and marathon runners - Vuorimaa, T.; Ahotupa, M.; Häkkinen, K.; Vasankari, T. (Scandinavian Journal of Medicine & Science in Sports, 2008)
In order to study the effects of different athletic backgrounds on exercise-induced hormonal responses, serum testosterone, luteinizing hormone, follicle-stimulating hormone and cortisol concentrations were measured before and after intensive continuous and intermittent running in well-trained middle-distance runners (MID) and marathon runners (MAR). They performed two 40-min exercises on a treadmill: a continuous run at an intensity of 80% [tempo run (TR)] and an intermittent run (IR) at an intensity of 100% of the velocity associated with VO2max. The testosterone response to IR and the cortisol response to TR was higher (P<0.05) in MID compared with MAR. The testosterone response to IR correlated positively with the maximal blood lactate concentration achieved after the maximal running test (r=0.46, P<0.05, n=20), while the cortisol response to TR correlated negatively with the runner's VO2max (r=-0.62, P<0.05, n=20). In conclusion, a continuous running exercise resulted in a lower cortisol response in runners who are adapted for longer distances, and an intermittent running exercise resulted in a higher testosterone response in runners who are adapted to middle distances.